Development of Juice Do It Business with Franchise Method: Strategy and Implementation (The Indonesian Journal of Business Administration, 2013)
The growth of the healthcare industry in Indonesia in recent years showed significant improvement. Health business grows rapidly with variety of different focus, such as health treatment, supplements, health assurance, medical equipment, health programs such as yoga and fitness center. Juice Do It, which was established on May 1, 2012 tried to address this opportunity by providing products of Juice that is loaded with health benefits. After operating for more than 1 year, Juice Do It showed significant progress with a positive market response and turnover increases. However, this does not necessarily make it stable in the industry. The market is constantly changing, new competitors continue to emerge everywhere. Market development should be done immediately. To address this issue, the authors will first analyze the internal and external conditions of this industry. With this analysis, it is expected that the development decisions can be planned better. From the analysis, it will be found the root of the problem of why the development should be done immediately. The proposed developmentâ€™s strategy were recommended by using the franchise method. To implement this method properly, the authors conducted a literature study on the franchise management and interviews with practitioners in the field. The overall strategies are carefully formulated using the relevant theory in the field. Several franchise packages are designed based on the budget of the franchise and the conditions in the field. Once the proposal is accepted by the management of Juice Do It, they will create a pilot project. The pilot project will serves as a place to apply theories that have been made as a pilot for the next outlet to be built.Â